Internalisasi Nilai Pendidikan Agama Islam pada Komunitas Anti Pengeras Suara di Kampung Talaga Rumpin Bogor - Abdul Azis; Jaenullah (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
This study aims to analyze the process of internalizing Islamic Religious Education (PAI) values within a community that rejects the use of loudspeakers in religious activities in Kampung Talaga, Rumpin District, Bogor Regency. This research employs a qualitative approach with a case study design. Data were collected through field observations and in-depth interviews with members of the community. The findings reveal that the community’s religious practices are strongly influenced by local wisdom values that emphasize inner tranquility, harmony with the natural environment, and harmonious social relationships among community members. These values serve as the foundation for the internalization of Islamic Religious Education values in their daily lives. The study indicates that local wisdom can function as an effective medium for strengthening the internalization of religious values within community life